PENGARUH PERSEPSI SISWA TENTANG PEMANFAATAN MEDIA PEMBELAJARAN BERBASIS ICT, KETERAMPILAN GURU DALAM MENGELOLA KELAS, DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR IPS TERPADU - Mada Angga Dwi Nata; Yon Rizal; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
This research’s goal is to know if there any influence of disciplinary learning, achievement motivation and attitudes of students towards teachers to economic studying result of first semester grade VII students of SMP Negeri 2Metro 2012/2013. To test the hypothesis first, second, and third using simple linear regression, while the fourth hypothesis using multiple linear regression.To test the first, second, and third hypothesis used simple linear regression and for the fourth hypothesis used multiple linear regression.The analysis result show that: (1) there is positive and significant influences of disciplinary learning to economic studying result (2) there is positive and significant influences of achievement motivation to economic studying result (3) there is positive and significant influences of the attitudesof students towards teachers to economic studying result (4) there is positive and significant influences of disciplinary learning, achievement motivation, and the attitude of studentstowards teachers to economic studying result.